Clinicoepidemiological profile and practices to manage dizziness in primary care setting: results from an Indian registry - Prabhat, Divya; Kiran, Ganga (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Dizziness is a common symptom encountered in primary care settings by general physicians and specialists. This study evaluated the clinicoepidemiological profile and management practices in patients with dizziness in an Indian primary care setting. Methods: This prospective, multicentric, observational study was conducted between November 2018 and June 2019. Patients aged≥18 years presenting with clinical features of dizziness were eligible. The study data included demographics and socioeconomic details, complete medical history, medication and concomitant medication use, and the cause and pattern of dizziness. Patients had a baseline visit and two follow-up visits at weeks 1 and 4. Results: Overall, 1000 patients with a mean age of 45.1 years were included (women: 51.5%; men: 48.5%). Of these, 762 reported dizziness as a primary complaint; whereas, 238 reported it as a complaint associated with nausea, vomiting and light-headedness on visit 1, which reduced on subsequent visits. Around 34% of the patients were unemployed and 59% belonged to the upper-middle class. The most common co-morbidities were hypertension and diabetes mellitus (n=132, each). More than 50% of the patients presented with vestibular cause (n=577), followed by neurologic (n=179), metabolic (n=84) and psychiatric (n=61) etiologies. Betahistine (n=581) and prochlorperazine (n=312) were the commonly prescribed medicines for primary and associated complaints. The most commonly used concomitant medications were telmisartan (n=53), glimepiride plus metformin (n=40), metformin (n=32) and ondansetron (n=29). Conclusions: Dizziness has a multifactorial origin necessitating a multifactorial treatment approach. Betahistine and prochlorperazine were the most commonly prescribed drugs in the primary care setting (CTRI/2018/11/016408).